A Single-Step Palladium-Catalysed Synthesis of Naphtho[2, 3-b]Benzofuran-6, 11-Diones and 2-(Hydroxyphenyl)Naphthalene-1, 4-Diones. (October 2017) - Gu, Binjie; Yu, Xiaoli; Xu, Zhaojun; Pan, Feng; Wang, Dawei
Palladium-catalysed competitive three-component C–H functionalisation reactions and cascade coupling ring-closing reactions of quinones with iodophenols in dihaloalkanes are described. During initial attempts to conduct C–H functionalisation reactions of quinones with iodophenols in dihaloalkanes, surprisingly a three-component C–H functionalisation reaction was discovered. Furthermore, as the reaction of chloroquinones with iodophenols was in progress, another surprising cascade coupling with ring closure was achieved. This provided an efficient single-step synthesis of naphtho[2, 3- b ]benzofuran-6, 11-diones.